2016
DOI: 10.1111/ajad.12483
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal and infant variants inPNOCandCOMTgenes with neonatal abstinence syndrome severity

Abstract: Background and Objectives There is significant variability in severity of neonatal abstinence syndrome (NAS) due to in-utero opioid exposure. Our previous study identified single nucleotide polymorphisms (SNPs) in the prepronociceptin (PNOC) and catechol-O-methyltransferase (COMT) genes that were associated with differences in NAS outcomes. This study looks at the same SNPs in PNOC and COMT in an independent cohort in an attempt to replicate previous findings. Methods For the replication cohort, full-term op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
1
36
0
5
Order By: Relevance
“…Percent methylation at each of the 20 CpG sites was determined. DNA was genotyped for OPRM1 118A>G (rs1799971) as part of a custom‐designed microarray at the BU Genomics laboratory …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent methylation at each of the 20 CpG sites was determined. DNA was genotyped for OPRM1 118A>G (rs1799971) as part of a custom‐designed microarray at the BU Genomics laboratory …”
Section: Methodsmentioning
confidence: 99%
“…NAS is a highly variable condition with genetic factors appearing to play a key role. Previous studies examined candidate genes and associations between single nucleotide polymorphisms (SNPs) and NAS severity, finding associations between variants in opioid receptor genes ( OPRM1 , OPRK1 , PNOC ) and stress response genes ( COMT ) and differences in NAS outcomes …”
Section: Introductionmentioning
confidence: 99%
“…A study by Wachman et al (2013) postulates that an association exists in NAS infants who possess specific SNPs in the COMT gene. This COMT gene is associated with the endogenous stress pathway and plays an essential role in opioid addiction and withdrawal (Wachman et al, 2017;Wachman & Farrer, 2019). Researchers found that the COMT gene and SNPs with the G allele in affected infants were associated with less need for pharmacologic treatment and shorter LOS due to a decrease in COMT enzyme activity (Cole et al, 2017;Wachman et al, 2013) (Table 1).…”
Section: Specific Genes and Neonatal Opioid Withdrawal Syndromementioning
confidence: 99%
“…28,29 Unique neonatal conditions like neonatal abstinence syndrome can be studied only in the newborn population, where outcomes have shown to be dependent on the genotype of the mother and the infant. 32 In addition, there is a dynamic temporal interplay between developmental and pharmacogenomic factors. Determining the age when genetic variations become the predominant factor for differences in drug response is crucial to evidencebased dosing algorithms in neonates.…”
Section: Effects Of Pharmacogenomics/ Pharmacogenetics On Pk/pdmentioning
confidence: 99%